Responsive Islamic Education in Exploring Social Values Through the War Takjil Phenomenon: Sociological Perspective in Indonesia - Minhaji, Minhaji; Hosaini, Hosaini; Prasetiyo, Nova Tri; Maktumah, Luluk; Alehirish, Mustafa Hamed Mohamed (JURNAL INDO-ISLAMIKA, 2024)
This research aims to explore the social values of Islam reflected in the phenomenon of "war takjil" in Indonesia through the method of Literature Review. "War takjil" is a practice where Muslim communities provide food for breaking the fast during Ramadan. The literature review method analyzes various textual sources, including articles, books, and scholarly writings relevant to this topic. The analysis is focused on understanding and interpreting the Islamic social values emerging within the context of "war takjil." Findings indicate that "war takjil" is not merely a religious tradition but also embodies Islamic values such as solidarity, compassion, and social care. Moreover, "war takjil" significantly strengthens social bonds and promotes unity within Indonesian Muslim communities. This research contributes to a deeper understanding of the relationship between religious practices and social values within the cultural context of Indonesia.